Strategi Dakwah Perempuan Berbasis Pemberdayaan Ekonomi - Faizah, Siti Inayatul (Ahsan: Jurnal Dakwah dan Komunikasi, 2023)
"Dakwah" not only speaks of religion, reading the Quran, but also concerns economic life, because this is one of the important factors in the life of Islamic households. Economic empowerment of women has a positive impact on improved family well-being. The economic resources women have, such as stable jobs and income, will be able to make a greater contribution to the family's economic needs. Therefore, economic empowerment should be one of the focuses of worship. So we need a women's empowerment-based strategy. This study is a library study of the efforts and strategies that can be taken to increase women's participation in economic empowerment. The results of this study show that economic empowerment of women can be achieved by providing education and training, broadening access to credit, building community networks and policies that favour women.